PARADIGMA INTEGRASI-INTERKONEKSI DI TENGAH KOMPLEKSITAS PROBLEM KEMANUSIAAN - Syahrial Labaso (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2018)
This article tries to describe the concept of integration-interconnection of science as a meeting point to integrating the mind and revelation. A concept which is positioning human mind and revelation as entities that are not dichotomous, but as relationships that complement to each other, as well as an effort to answer the complexity of the human problems which require a comprehensive and holistic process of settlement. Through critical-analytical studies of the concepts of integration-interconnection of science from various experts, the results of the study show that the term, forms, and implementations of this scientific paradigm are very diverse. Integration is not a single paradigm concept that is suitable in various life contexts, but a dynamic concept. The context in which human a being live will determine the patterns and forms of integration. Space and time, the types of problems and needs, and human creativity in responding the various life problems greatly determine the format and form of this paradigm.